Pengaruh Keadilan Organisasi Terhadap Kepuasan Kerja Dengan Personality (Kepribadian) Sebagai Variabel Pemoderasi (Studi Empiris Pada Dosen Perguruan Tinggi Swasta Di Kabupaten Kebumen) - Rohyani, Indah (Fokus Bisnis, 2014)
The research was conducted on Private Higher Education Lecturer In Kebumen with the title : "The Influence of Organizational Justice On The Job Satisfaction With Personality (Personality) As a moderating variable (Empiric Study on Private Higher Education Lecturer In Kebumen)". The study objective was to determine the effect of distributive justice , procedural justice and interactional on job satisfaction as well as find out if personality is able to moderate the influence of distributive justice , procedural justice and interactional on job satisfaction. The analytical tool used regression analysis and MRA. From the research and data analysis concluded that: Distributive justice, procedural and interactional positive and significant effect on the intrinsic satisfaction, and ekstrinsiks , high emakin distributive justice higher intrinsic and extrinsic satisfaction of faculty at private universities in Kebumen . Personality is made up of neuroticsm, extravertion, openess to experience, agreeableness and conscientiousness moderate the effect of distributive justice on job satisfaction intrinsic faculty at private universities in Kebumen. Personality is made up of neuroticsm, extravertion, openess to experience, agreeableness and conscientiousness did not moderate the effect of distributive justice on extrinsic job satisfaction. Personality is made up of neurotics, extravertion, openess to experience , agreeableness and conscientiousness did not moderate the effect of procedural justice on intrinsic job satisfaction. Personality is made up of neuroticsm, extravertion, openes to experience, agreeableness and conscientiousness did not moderate the effect of procedural justice on extrinsic job satisfaction. Personality is made up of neuroticsm, extravertion, openes to experience, agreeableness and conscientiousness, just extravertion able to moderate the effect of interactional justice on intrinsic job satisfaction. Personality is made up of neuroticsm, extravertion, openes to experience, agreeableness and conscientiousness, just extravertion and conscientiousness are able to moderate the effect of interactional justice on extrinsic job satisfaction. To increase employee job satisfaction both intrinsic and extrinsic the Private Higher Education in Kebumen pursue distributive justice in the implementation of its policies and emphasizes improving indicators : Organizations provide a fair reward based consider the magnitude of the employees job responsibilities. Organization of a fair reward employees based on consideration of the experience. Organization rewards its fair amount of effort employees. Organization of a fair reward for work well. Organization providing a fair appreciation of the level of stress and mental tension faced by employees in performing their duties. Additionally Private Colleges in Kebumen need to maintain procedural and interactional justice. Keywords : Personality neuroticsm, extravertion, openness to experience, agreeableness, conscienteiousness, distributive justice, procedural justice and interactional justice job satisfaction.